Eliza Smith: The Compleat Housewife: or Accomplished Gentlewoman's Companion - Davidson, Alan E (Petits Propos Culinaires, 2024)
Eliza Smith: The Compleat Housewife: or Accomplished Gentlewoman's Companion: a facsimile reprint of the 16th edition, 1758, by Arion House Publishing (Arion House, Station Road, King's Langley, Herts), 1983: [xxiv] + 394 + xii pp. with two folding plates, bound in leather, gilt top edge, £19.95.